The role that composition plays in determining how a viewer looks at landscape art - Tanya Beelders; Luna Bergh (Bern Open Publishing, 2020)
Viewing artworks may be subject to the same processes as everyday scene selection in respect of gaze behaviour. However, artists may employ carefully constructed composition in their paintings to lead the eyes of viewers along a predetermined path. This paper investigates whether composition is successful through comparison of expected scanpaths (constructed using the known intention of the artist) and actual scanpaths (as captured using an eye-tracker) based on a loci and sequence similarity index. The findings suggest that composition is successful in leading the eye, although the order of fixations can vary. It could thus be concluded that composition is largely successful in terms of salient elements, but less so for guiding elements. Furthermore, using Cognitive Linguistics theories and applying it to the paintings with reference to the statistical results, the Art Creation Continuum that captures the role of composition on a spectrum is proposed.